2019
DOI: 10.1007/s10919-019-00325-y
|View full text |Cite
|
Sign up to set email alerts
|

Was That a Scream? Listener Agreement and Major Distinguishing Acoustic Features

Abstract: Human screams have been suggested to comprise a salient and readily identified call type, yet few studies have explored the degree to which people agree on what constitutes a scream, and the defining acoustic structure of screams has not been fully determined. In this study, participants listened to 75 human vocal sounds, representing both a broad acoustical range and array of emotional contexts, and classified each as to whether it was a scream or not. Participants showed substantial agreement on which sounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…a harsh, thrilling, croaky sound) in the broad 30-150Hz range that contributes to the alarming quality of fear screams [19]. Other studies confirmed that roughness, amongst other important acoustic and perpetual features, is a defining perceptual feature of screams that enable listeners to classify vocalizations as screams [3].…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…a harsh, thrilling, croaky sound) in the broad 30-150Hz range that contributes to the alarming quality of fear screams [19]. Other studies confirmed that roughness, amongst other important acoustic and perpetual features, is a defining perceptual feature of screams that enable listeners to classify vocalizations as screams [3].…”
Section: Introductionmentioning
confidence: 92%
“…The recordings of the neutral and the 6 generic scream types resulted in a total of 420 acted scream calls that are acoustically similar to natural screams [1,2]. The screaming quality of these vocalizations was verified by ear by trained senior members of the research team, since clear formal acoustic criteria for scream calls are not yet established [3]. Scream calls are also easily identified and discriminated from other nonverbal affective vocalizations [21].…”
Section: Psychoacoustic and Affective Diversity Of Human Screamsmentioning
confidence: 99%
See 3 more Smart Citations